Integrated System of Sedimentation, Grease Trap and Adsorption For Oil And Grease Reduction In Workshop Wastewater - Siswati, Hesti; Irfa'i, Muhammad; Pahruddin, Muhammad (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Workshops are significant sources of hazardous wastewater, classified as B3 waste due to the presence of toxic compounds that can endanger the environment and human health. This study aimed to design and evaluate a treatment system for workshop wastewater using sedimentation, grease trap, and adsorption processes. An experimental pretest–posttest with control group design was employed, involving 24 samples and six repetitions. Data were analyzed using the Kruskal–Wallis test to determine differences in oil and grease reduction across various contact times with activated carbon. Statistical analysis showed a p-value of 0.413 (>0.05), indicating no significant difference among contact time variations. The most effective treatment, combining sedimentation, grease trap, and adsorption, achieved an oil and grease concentration of 3.7 mg/L with a 15-minute contact time and 1000 mL activated carbon, corresponding to a 99.96% removal efficiency. This contact time was considered optimal when factoring in both performance and manufacturing cost. The findings demonstrate that while contact time variation did not significantly affect removal efficiency, the integrated process effectively reduced oil and grease to levels compliant with environmental standards. The developed system can serve as a low-cost alternative for small-scale workshops to manage liquid waste, minimizing environmental and health risks. Future studies are recommended to evaluate additional parameters such as total suspended solids (TSS), chemical oxygen demand (COD), and biological oxygen demand (BOD) for a more comprehensive assessment of treatment performance.